The Influence of Augmented Reality Integrated Educational Games on Student Motivation in Islamic Education - Nilam Nastiti Normala Dewi; Sugiono; Hasan Baharun; Annisa Tri Ananda Dewi (Seutia Hukamaa Cendekia, 2025)
This study aimed to examine the influence of augmented reality (AR) integrated educational games on student motivation in Islamic Education (PAI) classrooms. The research employed a qualitative case study design, conducted in selected schools in East Java, Indonesia, where AR-based gamified learning had been implemented. Data were collected through semi-structured interviews with teachers and students, classroom observations, and document analysis, and were analyzed using data condensation, display, and verification techniques to ensure credibility. The findings indicate that AR-integrated educational games significantly enhance intrinsic motivation by providing immersive, interactive, and narrative-driven experiences, while also fostering extrinsic motivation through gamification elements such as points, badges, and challenges. Students demonstrated higher engagement, perseverance, and collaborative behaviors, and educators reported improved understanding and participation in PAI lessons. The study contributes to educational theory by extending frameworks of motivation and digital learning to religious education contexts and offers practical implications for designing interactive, technology-enhanced pedagogy that supports both cognitive and socio-emotional development in students.